2021
DOI: 10.3390/membranes11050368
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Permeate Flux in Ultrafiltration Processes: A Review of Modeling Approaches

Abstract: In any membrane filtration, the prediction of permeate flux is critical to calculate the membrane surface required, which is an essential parameter for scaling-up, equipment sizing, and cost determination. For this reason, several models based on phenomenological or theoretical derivation (such as gel-polarization, osmotic pressure, resistance-in-series, and fouling models) and non-phenomenological models have been developed and widely used to describe the limiting phenomena as well as to predict the permeate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 202 publications
(292 reference statements)
1
18
0
1
Order By: Relevance
“…We concur with [9] that CP is a reversible phenomenon. Indeed it is suggested that the statement "CP is considered as a reversible phenomenon" be strengthened so as to state that CP is a reversible phenomenon.…”
Section: Is Concentration Polarisation the Primary Reason For Flux De...supporting
confidence: 84%
See 3 more Smart Citations
“…We concur with [9] that CP is a reversible phenomenon. Indeed it is suggested that the statement "CP is considered as a reversible phenomenon" be strengthened so as to state that CP is a reversible phenomenon.…”
Section: Is Concentration Polarisation the Primary Reason For Flux De...supporting
confidence: 84%
“…Also as pointed out by others the supposedly constant value of C gel . seems to vary during filtration [9,16,17].…”
Section: Can Gel Theory Explain Flux Decline?mentioning
confidence: 99%
See 2 more Smart Citations
“…By using the generalized mBLA method, spatially resolved UF concentration and flux profiles are determined in addition to their spatial averages, based on theoretically precise and experimentally well-tested expressions for the dispersion properties. In case one is interested in spatial averages only, e.g., in order to compare with experimental data for the length-averaged permeate flux and TMP, a number of more simple methods are given in the literature as summarized in [2,46]. The mBLA method in its present form deals with generic CP layer effects only.…”
Section: Remarks On the Generalized Mbla Methodsmentioning
confidence: 99%